Diagnosis and Therapeutic Management of Myxomatous Mitral Valvular Degeneration (MMVD) in Daschund Dog – A Case Report - Parmar, Saurabh; Patel, Manish; Vala, Jignesh; Mehta, Sudhir; Mavadiya, Suresh (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
Myxomatous mitral valve disease (MMVD) is considered to be the most common heart disease of dogs globally.Approximately 30% of dogs over 10 year’s age possess the characteristic left-sided systolic murmur of degenerative DMVD and resulting mitral regurgitation (Buchanan, 1977). It is estimated that approximately 10% of dogs presented to primary care veterinary practices have heart diseases and congenital valvular heart diseases (CVHD) is the most common heart disease among them (Atkins et al., 2009). The myxomatous degeneration of the mitral valve accounts for approximately 75% of heart disease and affects mostly smallto medium sized breeds, although large breeds have also been reported.